Adapting from the Internet: Cultural adaptation in Teh Internet is Serious Business. (1st May 2016) - Nicholas, Tom
This article argues that the Internet today constitutes a social and cultural space, holding within it a culture distinct from that of the physical world with its own customs, morals and beliefs. Taking as a case study Tim Price's Teh [sic] Internet is Serious Business, which premiered at the Royal Court Theatre in September 2014, it will use Patrice Pavis' 'hour-glass' model to carry out a textual analysis of this adaptation of the factual story of the formation of online activist groups Anonymous and LulzSec for presentation within the theatrical form of contemporary Britain, a narrative which has become one of Internet Culture's major cultural myths.